The European Union's Position in International Trade - Valentina BUTMALAI; Alina Florentina SĂRACU, Dr (ACROSS, 2022)
In terms of trade, the European Union is at the fore. The European Union is now the biggest player in the global trade scene as a result of the opening up of the trade regime, and it is still a favorable location for business. Trade development is a chance for economic growth. Therefore, through expanding trade and investment opportunities with the rest of the world, the European Union's trade policy aims to promote growth and the creation of jobs. Together, Europe has the ability to create an open, fair, global economic system and ensure that the rules are upheld. The prosperity of the European Union's economic partners in both the developed and developing worlds is intimately connected to that of the European Union. Through trade agreements, the European Union controls its trading connections with other nations. They are made to improve commercial possibilities and lower trade obstacles. Along with the protection of European companies and consumers, the promotion of EU ideals and values is one of the most crucial components of the EU's trade policy. Sustainable development is crucial for trade policy because of this. More than just removing tariffs is involved in free and open commerce. It also includes the elimination of non-tariff restrictions like import permits, valuation guidelines for customs, pre-shipment inspections, or certification processes. Consumers benefit from lower prices and higher value thanks to trade without these frictions. Not only that, but trade agreements that channel foreign investment also significantly increase employment. The aim of the study is to determine the position of the European Union in international trade and what has been the evolution of this position in recent years.